From data to knowledge a method for modeling hospital logistic processes. - Maruster, L.
When modeling or redesigning a process, the knowledge-management perspective is seldomly used. Using the knowledge categorization developed by van Heusden and Jorna, we propose a knowledge-management perspective to provide a strategy for modeling and redesigning a business process. As an illustration of our approach, we use hospital data of multidisciplinary patients. This specific group of patients requires the involvement of different specialisms for their medical treatment that leads to more efforts regarding the coordination of care for these patients. In order to increase the care efficiency, knowledge that supports the reorganization of care for multidisciplinary patients should be provided. We use the above-mentioned knowledge-management perspective for creating new multidisciplinary units, in which different specialisms coordinate the treatment of specific groups of patients.
Keywords: Business process redesign; Care efficiency; Clustering; Hospital data; Hospital logistic process modeling; Knowledge categorization; Knowledge type; Knowledge-management.; Medical treatment; Multidisciplinary patient care; Process discovery